On the relative role of climate change and management in the current desert locust outbreak in East Africa. (16th May 2020) - Meynard, Christine N.; Lecoq, Michel; Chapuis, Marie‐Pierre; Piou, Cyril
Abstract : While large‐scale monitoring, early detection and control can greatly reduce desert locust invasions, global change is most likely to affect conditions that promote the transition from solitary to gregarious populations. Although climate change scenarios point to an increase in aridity and further desertification in vast areas of Africa, some regions that have been at the origin of past outbreaks are likely to see a reversed trend (i.e., increase in frequency and intensity of rains), potentially favoring the formation of swarms. This makes reinforcing early detection and keeping a sustained monitoring effort in place even more important under climate change.